Exploring the influence of collaborative leadership on Grade 12 mathematics results in a low-resourced secondary school - Hendri J. Theron (African Journal of Career Development)
Background: This case study examines the role of collaborative leadership in Grade 12 Mathematics results. The article challenges the notion that collaborative leadership is not a significant factor in improving Grade 12 Mathematics results, particularly in low-resourced secondary schools in South Africa.